Población de Crocodylus acutus (Crocodylia: Crocodylidae) en dos ríos de Costa Rica - Sánchez R., Juan J; Bolaños, Juan R; Piedra C., Lilliana (Revista de Biología Tropical, 1996)
Spatial distribution and population size of Crocodylus acutus were estimated during December 1992-March 1993 in the Tempisque and Bebedero rivers, Guanacaste, Costa Rica. Along 47 km, 138 crocodiles were seen: 2.9 indlkm in Tempisque; 4.5 indlkm in Bebedero. The total length distribution in Tempisque (divided in areas B, C and D) presents individuals in Size 1 (hatchlings) in area B. Size II (recruits) were mainly found in area C, together with sizes III and VII (juveniles and adults). Area D lacked with sizes IV and VII. In Bebedero most were juveniles. Animals were noticed mainly for their "eyes": 48% to size 1, 36% to size IlI. Sexualy mature individuals were concentrated in areas C and D, and were 12.3% of the observed animals. The size distribution, without considering the "eyes" cIass, was 3% hatchlings, 24.2 recruits, 30.3% juveniles and 3% adults in Bebedero; and 13%, 12.3%, 14.5% and 12.3% respectively in Tempisque.